Golden Gallery's Business Development Strategy Based on Sharia Financing Needs through Partnerships and a Marketing Mix of Services - Muhammad Hafizhan Fakhri; Zuhrinal M Nawawi; Tuti Anggraini (Majapahit Journal of Islamic Finance and Management, 2026)
This study analyzes the business development of Golden Gallery, an MSME operating in the bridal gown rental service, which faces limited business capacity, particularly in terms of the quantity and variety of its fashion collections amid increasing competition in the wedding service industry. The research focuses on evaluating the service marketing mix, business partnerships, and the feasibility of Islamic financing as strategic efforts to support business expansion. A mixed methods approach with a case study design was employed, utilizing in-depth interviews and consumer questionnaires as supporting data. The findings indicate that Golden Gallery demonstrates strong marketing performance with a high level of customer satisfaction. However, limitations in fashion collections remain a major constraint in meeting market demand. From an Islamic banking perspective, Golden Gallery is considered eligible for financing through a murabahah scheme to enhance business capacity, strengthen competitiveness, and ensure business sustainability. These findings reinforce the importance of Islamic financing approaches that are grounded in the strategic needs of MSMEs rather than solely financial considerations.